Interaction between rifampin and fusidic acid against methicillin-resistant coagulase-positive and -negative staphylococci. - Farber, B F (1986)
We studied the interaction between rifampin and fusidic acid against a group of staphylococci. Of the 20 coagulase-positive strains studied, checkerboard studies revealed synergy in 3 and indifference in 17; time-kill studies revealed synergy in 18 of 19 coagulase-positive strains at both 24 and 48 h. Of the 19 coagulase-negative strains, checkerboard studies revealed synergy in 6 and indifference in 13; time-kill studies revealed synergy in 6 of 18 coagulase-negative strains at 24 h and in 17 of 18 coagulase-negative strains at 48 h. The combination of rifampin and fusidic acid warrants further evaluation in the therapy of staphylococcal disease.